2021
DOI: 10.2147/dddt.s314076
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Rescues Cognitive Dysfunction, Mitigates Neurodegeneration, and Exerts Anti-Epileptic Effects Through Activating TLR4/MYD88/Caspase-3 Pathway in Rats

Abstract: This study aims to evaluate the beneficial effects of anti-epileptic mechanisms of baicalin (BA) on cognitive dysfunction and neurodegeneration in pentylenetetrazol (PTZ)induced epileptic rats. Methods: First, PTZ-induced epileptic rats were administered intraperitoneally a subconvulsive dose of PTZ (40 mg/kg) daily, and the seizure susceptibility (the degree of seizures and latency) was evaluated using Racine's criterion. Then, classical behavioral experiments were performed to test whether BA ameliorated cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…The mechanisms involved in the neuroprotective effects might be related to the increased level of glutathione (GSH) and activity of superoxide dismutase (SOD), reduced expression of pro-inflammatory factors in the hippocampus and regulation of apoptosis-related genes. The antiepileptic effects of Baicalin are effectuated via activation of the TLR4/MYD88/Caspase-3 pathway ( 69 , 70 ). Also, it has a significant therapeutic effect on the rat model with epilepsy phenotype similar to TLE patients, which improves the cognitive impairment and hippocampal injury by inhibiting oxidative stress and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in the neuroprotective effects might be related to the increased level of glutathione (GSH) and activity of superoxide dismutase (SOD), reduced expression of pro-inflammatory factors in the hippocampus and regulation of apoptosis-related genes. The antiepileptic effects of Baicalin are effectuated via activation of the TLR4/MYD88/Caspase-3 pathway ( 69 , 70 ). Also, it has a significant therapeutic effect on the rat model with epilepsy phenotype similar to TLE patients, which improves the cognitive impairment and hippocampal injury by inhibiting oxidative stress and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Another study highlighted that 8 inhibits activation of the GSK3β/NF-κB/NLRP3 signal pathway and shows remarkable neuroprotective effects in a rat model of depression. 72 Zhang et al 73 explored that 8 was able to promote neuronal differentiation and survival through the Akt/FOXG1 pathway and could reverse the reduction of p -Akt, FOXG1, and FGF2 caused by chronic unpredictable mild stress (CUMS)-induced depression; it was also supported by the study of Fang et al 74 Recent studies highlighted that 8 acts through several pathways such as the BDNF/ERK/CREB signaling pathway, 75 Wnt/β-catenin pathway, 76 and activation of TLR4/MYD88/caspase-3 pathway 77 to improve cognitive dysfunctions induced by CUMS and promotes neurogenesis in an animal model of depression. Recently, Li et al 78 explored 8 to analyze its antiepileptic effects and found that it exhibited a significant antiepileptic effect by regulating astrocyte phenotype to maintain systemic homeostasis.…”
Section: Chromones With Anti-neurodegenerative Propertiesmentioning
confidence: 88%
“…Some studies showed that the TLR4 signaling pathway produces an antiepileptic effect. Yang et al (32) successfully established an epileptic model and built a pharmacological network, which found that the hippocampus experienced in the epilepsy group contained an upregulation of TLR4, MYD88, and Caspase-3 compared with the control group counterparts. Zhu et al (33) showed that blocking TLR4/MYD88 signaling attenuated KA-induced neuroinflammation and neuronal damage in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%